Study on the preparation of sterile noble metal nanoparticles and hydrotalcite layered nanoparticles by innovative high pressure sterilization method - Zhihua Xu; Renyin Zhang; Tongtong Zhang; Zhihan Niu; Min Zhang; Feng Shi (Scientific Reports)
Abstract We have developed an innovative nanoparticle preparation technique. It utilised a high-pressure steam sterilisation pot as the reaction equipment, simplifying biomedical nanoparticle synthesis and sterilisation processes. Gold nanoparticles (AuNPs), silver nanoparticles (AgNPs), and two types of hydrotalcite-layered nanoparticles (LDHs) were prepared successfully. The nanoparticles had a regular morphology and good dispersion, which is consistent with the characteristics of products prepared using traditional methods. The average particle sizes of AuNPs and AgNPs were 25 and 38 nm. Ultraviolet absorption peaks of AuNPs and AgNPs were observed at 520 and 436 nm, respectively. The average particle sizes of the LDHs used for anion and cation intercalation were 82 and 90 nm, respectively. The elemental composition of the LDHs included Co, Mg, Al, C, and O. Functional group characterisation results showed that the surfaces of the four nanoparticles contained abundant functional groups. The high-pressure sterilisation method used in this study produced sterile nanoparticles with good performance in a single step. It avoided the problems associated with the physicochemical property changes in the nanoparticles caused by the secondary sterilisation operations, thereby ensuring their usability in biomedical applications. Thus, the method provides a scalable synthesis pathway for nanotechnology and inspiration for further research on nanotechnology.